KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DALAM PENINGKATAN KUALITAS PELAKSANAAN EVALUASI PEMBELAJARAN DI MI SA'ADATUDDARAIN - Syarifah Usma (UNISAN JURNAL, 2024)
The point of this exploration is to decide the expert capability of Islamic Strict Schooling educators in the growing experience at MI Sa'adatuddarain, Pekayon, Pasar Rebo, East Jakarta. This exploration is remembered for the kind of field research which is subjective in nature, audits techniques and levels of conversation, so this examination is named elucidating research. Information assortment strategies in this exploration utilized perception techniques, interview strategies and documentation strategies. Show of information in this examination is information assortment, information show, and reaching determinations. In view of the examination results, it very well may be presumed that all expert skills have had the option to be executed ideally in spite of the fact that there is as yet a requirement for development in all pointers. Of the five marks of expert ability that have been effectively carried out well and ideally, it is the utilization of learning media/innovation. The aftereffects of the examination show that class instructors at MI Sa'adatuddarain, Pekayon, Pasar Rebo, East Jakarta are truly adept at utilizing learning media/innovation going from slides, books, type-recorders, tapes, PCs, movies and LCD projectors. , all pre-owned well and methodicallly as indicated by the material to be introduced. Class educators are likewise exceptionally sharp in picking learning media so that learning runs successfully, productively and pleasant in light of the fact that an expert instructor isn't simply expected to dominate the learning material that will be conveyed to his understudies, yet in addition should have the option to pick the right one. media and ready to use media as per the qualities of open materials.